Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/1756-9966-30-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hyperthermia and adrenaline to enhance the intratumoral accumulation of cisplatin in a murin model of peritoneal carcinomatosis

Abstract: BackgroundThe best method to deliver intraperitoneal chemotherapy (IPC) for peritoneal carcinomatosis from ovarian cancer is not well defined. The aim of this study was to assess the ability of hyperthermia and adrenaline to enhance the intratumoral accumulation of cisplatin in a rat model of peritoneal carcinomatosis.MethodsFour groups of 5 BDIX rats with ovarian peritoneal carcinomatosis underwent IPC with 30 mg/l of cisplatin according to the following conditions: normothermia at 37° for 1 or 2 hours, hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
(43 reference statements)
0
15
0
1
Order By: Relevance
“…Tumors are usually heated to the temperature range of 41-47°C, and cancer tissues exhibit higher heat sensitivity than normal tissues [20]. It also has been believed that the drug delivery to target could be increased by hyperthermia through its effects on convection and diffusion in tissues, increasing cell uptake of the drug, tumor blood flow and vascular permeability [21]. In our study, Resovist or the Resovist/doxorubicin complex also induced temperature increases to approximately 41°C ( Figure 5A).…”
Section: Discussionmentioning
confidence: 65%
“…Tumors are usually heated to the temperature range of 41-47°C, and cancer tissues exhibit higher heat sensitivity than normal tissues [20]. It also has been believed that the drug delivery to target could be increased by hyperthermia through its effects on convection and diffusion in tissues, increasing cell uptake of the drug, tumor blood flow and vascular permeability [21]. In our study, Resovist or the Resovist/doxorubicin complex also induced temperature increases to approximately 41°C ( Figure 5A).…”
Section: Discussionmentioning
confidence: 65%
“…9,[14][15][16][17][18][19][20] However, comparisons between these methods are lacking, as are pharmacokinetic and pharmacodynamic data to prove their effect. Furthermore, the results obtained with one drug are not necessarily the same as those with another.…”
Section: Tissue Concentration Of Oxaliplatinmentioning
confidence: 98%
“…Hyperthermia is widely used to this end, even though it is not effective with all chemotherapy drugs. [7][8][9] Five years ago, our group showed that high pressure closed intraperitoneal chemotherapy with cisplatin increased cisplatin penetration into the peritoneum, and increased survival in rats with peritoneal carcinomatosis of colorectal origin. 10 As open techniques of HIPEC might achieve better tissue concentrations than closed techniques according to a previous experimental work, 11 we hypothesized that high pressure could be achieved during open HIPEC.…”
mentioning
confidence: 99%
“…A lot of studies have explored the potential of platinum-based combination therapy [19] that means to combine one, two or more known non-platinum anticancer drugs with a platinum compound, for example [20][21][22][23][24][25]. Such a combination leads to synergistic effects and/or to lowering toxicity of platinum-based drugs and is very promising in cancer chemotherapy.…”
mentioning
confidence: 99%